Cosmetología facial y su incidencia en el aprendizaje pragmático de las estudiantes de belleza del centro de formación artesanal 15 de octubre del cantón Naranjal, Provincia Guayas - Galarza Barros, Patricia del Carmen (2021)
Through the following research work that had the objective of understanding the importance of the study of facial cosmetology in how many criteria and values, it is necessary to determine that a tour of different notions of this method was carried out in order to begin to carry out an analysis of control, which helped us to introduce timely changes according to the evolution of and the aesthetic alteration that we are treating, Certainly the need to look physically well, the variety of cosmetics that exist for every need of people. According to the needs of cosmetology, it can be used individually or combined according to the needs of our patients, it is the most important phase where it will be violated to use techniques that its objective is to improve and give a lifestyle taking into account the need of the demand for the subject. of beauty is constantly advancing in a world where modern, where society through being well raises its self-esteem, the values of health and the constantly active physique. Likewise, the hypothesis was verified. If Facial Cosmetology is analyzed, will it affect the Pragmatic Learning of the beauty students of the Artisan Training Center October 15 of the Naranjal Canton of the Guayas Province?